IN VITRO STUDIES ON LUFFA ACUTANGULA LIN. VAR. AMARA. ROXB - AN IMPORTANT MEDICINAL PLANT. - R. SYED MOIDEEN; A. LAKSHMI PRABHA (International Journal of Pharma and Bio Sciences, 2014)
Luffa amara is an important wild medicinal plant belongs to the family Cucurbitaceae. All parts of the plants are crystalline bitter compound with cucurbitacin B and Amarinin. The whole plant is used to cure many diseases, especially in anti-cancer, anti-diabetic, anti-jaundice and many ailments. The present study, deals with the callus induction, multiplication of luffa from the nodal, leaf and petiole explants. Different concentrations of auxins and cytokinins were used for callus induction and their fresh and dry weights were measured. Best callus induction was observed in the concentration of 2, 4 – D + TDZ – 1.5 mg/l. higher percentage of fresh and also dry weight callus was obtained in the medium fortified with 1.5 mg/l (2, 4 – D + TDZ). mg/l.